Kolesterol Total dan Kolesterol LDL terhadap hsCRP pada Pasien COVID-19 Berat - Irawaty, Noni; Syafril, Santi; Loesnihari, Ricke (Journal of Telenursing (JOTING), 2023)
This study aims to examine the relationship between total LDL cholesterol and hsCRP in severe COVID-19 patients at the H. Adam Malik Hospital, Medan. The research method used was a cross-sectional retrospective study. The research results showed a negative correlation between Total Cholesterol and LDL Cholesterol and hsCRP in severe COVID-19 patients. In conclusion, a decrease in Total Cholesterol and LDL Cholesterol levels was found in severe COVID-19 patients. Increased hsCRP levels were found in severe COVID-19 patients. The demographic characteristics of the research subjects were dominated by male patients. The most common comorbidity found is Diabetes Mellitus Type 2, followed by hypertension. Keywords: Severe COVID-19, hsCRP, LDL Cholesterol, Total Cholesterol